2007
DOI: 10.1183/09031936.00010206
|View full text |Cite
|
Sign up to set email alerts
|

Weaning from mechanical ventilation

Abstract: Weaning covers the entire process of liberating the patient from mechanical support and from the endotracheal tube. Many controversial questions remain concerning the best methods for conducting this process. An International Consensus Conference was held in April 2005 to provide recommendations regarding the management of this process. An 11-member international jury answered five pre-defined questions. 1) What is known about the epidemiology of weaning problems? 2) What is the pathophysiology of weaning fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
1,499
7
200

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,658 publications
(1,847 citation statements)
references
References 227 publications
24
1,499
7
200
Order By: Relevance
“…Compared with the previous literature, the lower weaning success rate in our study is probably related to the heterogeneity of our study population and to the specific PMV nature of our subjects. 9 We have confirmed that patients in a protected environment present a low mortality risk with a weaning rate of Ͻ 50%. We have also shown that tracheostomy and stay in a chronic ventilator facility do not affect mortality, weaning, or their timing.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Compared with the previous literature, the lower weaning success rate in our study is probably related to the heterogeneity of our study population and to the specific PMV nature of our subjects. 9 We have confirmed that patients in a protected environment present a low mortality risk with a weaning rate of Ͻ 50%. We have also shown that tracheostomy and stay in a chronic ventilator facility do not affect mortality, weaning, or their timing.…”
Section: Discussionsupporting
confidence: 62%
“…1 Indeed, this condition may increase risk of early mortality 5,6 and late pulmonary complications, 7 involving increased health costs. 8 Patients needing prolonged mechanical ventilation (PMV) 9 may require transfer to a protected environment such as a chronic ventilator facility, 3,10 which studies have shown can offer some clinical and financial advantages over a prolonged ICU stay. 3,11,12 In particular, patients may receive a prompt and dedicated physiotherapy rehabilitation program in chronic ventilator facilities, 1,3,13 and transfer from an ICU to a chronic ventilator facility substantially improved patients' ambulation and activities of daily life irrespective of the underlying pathophysiology, avoiding unnecessary immobilization 14 . To date, the role of comprehensive rehabilitation in critically ill adults still remains controversial 13 or not fully established 15 : patients who have survived a recent acute respiratory failure (ARF) event can benefit from an individually tailored physiotherapy rehabilitation program that improves clinical indices, respiratory and peripheral muscle strength, activities of daily life, exercise tolerance, and disability scores.…”
Section: Introductionmentioning
confidence: 99%
“…According to Coplin et al 7 , delayed extubation was associated with a statistically signifi cant increase in mortality (RR for death 2.2, 95% CI: 1.0-4.7). Boles et al 1 have proposed the early investigation of weaning capacity to avoid its delay.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a predictor, such as the rapid shallow breathing index (RSBI), is initially used as screening and if the result is positive for weaning success, a spontaneous breathing trial (SBT) is started. If the patient passes this test, MV is discontinued and followed by extubation 1 . The problem is that, despite all systematization of the weaning process, backed by different studies that establish the various steps of this process, the average rate of weaning failure is 30%, which is associated with increased morbidity and mortality [1][2][3][4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation